Demographic, Clinical and Laboratory Characteristics of Ocular Syphilis: 6-Years Case Series Study From an Eye Center in East-China - Sun, Chuan-bin; Liu, Geng-hao; Wu, Rong; Liu, Zhe (Frontiers in Immunology, 2022)
Purpose To report the demographic, clinical, and laboratory characteristics of ocular syphilis based on a 6-year case series study from an eye center in East-China. Methods A total of 131 cases (191 eyes) of ocular syphilis and the annual number of total syphilis cases from January 2016 to December 2021, were included in this study. Detailed medical records including systemic and ophthalmic medical history, a complete ophthalmic examination, color fundus photography, B-type ultrasound, fundus fluorescein angiography (FFA), spectral domain optical coherence tomography (SD-OCT), laboratory tests of the serum and cerebrospinal fluid (CSF) samples, as well as visual field test and orbital or cranial MRI in cases with suspected optic neuritis or optic atrophy, were collected and analyzed. Pearson Chi-square or Fisher’s exact tests was used for statistics analysis. Results Of the 131 cases with ocular syphilis, 86 cases were in men and 6 cases had a past medical history or systemic manifestation of syphilis. HIV was found in only 2 of 70 cases undergoing serum HIV test. The average age was 54.0 years, ranging from 26–85 years. The average percentage of ocular syphilis out from the total syphilis cases was 5.1%, the average titer of serum rapid plasma regain (RPR) at presentation was 1:32, ranging from 1:1–1:512. The most predominant manifestation of ocular syphilis was posterior uveitis, followed by optic neuritis, optic atrophy, panuveitis, retinal vasculitis, and retinitis. The median of BCVA of all 191 eyes was 20/200 (ranging from no light perception to 20/20), and 20/40 (ranging from no light perception to 20/20) at presentation and final follow-up, respectively. Ocular syphilis with active inflammation responded well to penicillin therapy, no matter the initial visual acuity, ocular disease type, or RPR titers, as long as it was diagnosed early and treated properly and promptly. However, cases with optic atrophy, acute retinal necrosis, late diagnosis, permanent disruption, or loss of outer segment of photoreceptors of macular retina on SD-OCT showed poor visual improvement after therapy. Conclusions Early diagnosis of ocular syphilis is still challenging in clinical practice and syphilis tests should be routinely performed in patients with uveitis, retinitis, optic neuritis, and optic atrophy.